Sustainable agricultural practices : economic and environmental implications - Das, Ramash Chandra (Emerald Publishing Limited, 2024)
An increase in the global population has led to a higher demand for food, besides complicating environmental, economic, and social issues. Agricultural industries across the world have adopted modern technologies to boost yields, but these methods frequently cause environmental harm due to the use of chemical fertilizers, pesticides and insecticides. While the 'green revolution' has enhanced food security for numerous regions, it has also worsened the qualities of the environmental assets. Sustainable Agricultural Practices: Economic and Environmental Implications presents a comprehensive exploration of contemporary challenges and innovative solutions in agriculture. From analysing the impact of total factor productivity (TFP) on environmental sustainability to investigating trade relationships among BIMSTEC countries (India, Bhutan, Bangladesh, Myanmar, Thailand, Nepal, Sri Lanka), this collected edition delves into some of the most important agricultural questions today. Chapters cover diverse topics such as food waste, unemployment and flood response in Bangladesh, as well as the implications of agricultural growth on food security in India and Pakistan. With contributions from scholars worldwide, this collection offers valuable insights into the intricate nexus between agricultural, environmental and socio-economic dynamics, fostering informed policies and practices for a sustainable future. This comprehensive collection provides insights for researchers and academics in agriculture and environmental studies. Policy makers and government officials, as well as international development practitioners, may also reap benefits from the analysis of food security issues, environmental health and socioeconomic development.
Includes index.
Keywords: Sustainable agriculture.; Business & Economics -- Development -- Sustainable Development.; Agriculture, agribusiness and food production industries.; Development economics and emerging economies.; Sustainability.; elektronické knihy; electronic books